Prospective study on the prevalence of HCV infection in consecutive adult inpatients in a hospital division of Internal Medicine in Tuscany. (March 2023) - Pacini, S.; Capecchi, P.L.; Brillanti, S.
Abstract : Introduction: Prevalence of HCV infection in adults in Italy ranges between 0.5 and 3% across the country. Free HCV screening is offered to subjects born after 1969, but little is known about the prevalence of HCV infection in elder subjects. Aim: This prospective study aimed to evaluate the prevalence and significance of HCV infection in consecutive adult inpatients without a history of hepatitis C during their stay in a large division of Internal Medicine in Tuscany. Materials and Methods: Between October 2021 and July 2022, all the consecutive adult inpatients born before 1969, without a history of hepatitis C, and admitted to the Division of Internal Medicine at the University Hospital in Siena (AOU Senese) were tested for antibody to HCV (anti-HCV). In addition, demographic characteristics and liver test results were collected. Results: A total of 571 consecutive adult patients (307 males, 264 females) without a history of hepatitis C were evaluated. Median age was 82 yrs. (range: 52 - 99). Unknown HCV infection was detected in 12 patients (2.1%). Characteristics of the HCV-positive patients are summarized as follows (values are expressed as median and range):Sex (M/F): 7/5, Age (yrs): 74 (54 – 84), AST (IU/L): 25.5 (14 – 163), ALT (IU/L): 19 (11 – 89), Bilirubin (mg/dL): 0.8 (0.2 – 3.3) Among the 12 HCV-positive patients without a history of hepatitis C, clinical signs of liver cirrhosis were present in 1, and hepatocellular carcinoma was first detected in another patient. Conclusions: Routine detection of anti-HCV in all adult inpatients consecutively admitted in a division of Internal Medicine in a large hospital in Tuscany allowed estimation of a 2.1% HCV infection prevalence rate. Evidence of advanced liver disease was not found in many of them but let the detection of previously undiagnosed clinically significant liver cirrhosis and hepatocellular carcinoma.